2022
DOI: 10.1039/d1bm01657a
|View full text |Cite|
|
Sign up to set email alerts
|

Hierarchical microgroove/nanopore topography regulated cell adhesion to enhance osseointegration around intraosseous implants in vivo

Abstract: Implant surface topography plays a crucial role in achieving successful implantation. Simple and controllable surface topographical modifications are considered a promising method to accelerate bone osseointegration for biomedical application. Moreover,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…48 Although it has been reported that integrin α2 can also regulate the osteogenic differentiation of MSCs through the phosphatidylinositol 3 kinase (PI3K)/protein kinase B (Akt) pathway, this external regulator is determined by ECM morphology rather than matrix stiffness. 49 Integrin β1 can activate the phosphorylation of FAK, which then leads to the activation of downstream intracellular signaling pathways, such as Ras/ mitogen activated protein kinase (MAPK), PI3K/Akt signaling pathways, etc. 50,51 In addition, studies have found that laminin proteins regulate the early osteogenic differentiation of stem cells by regulating the integrin α2β1 and FAK/extracellular regulated protein kinases (ERK) signaling pathways.…”
Section: Papermentioning
confidence: 99%
“…48 Although it has been reported that integrin α2 can also regulate the osteogenic differentiation of MSCs through the phosphatidylinositol 3 kinase (PI3K)/protein kinase B (Akt) pathway, this external regulator is determined by ECM morphology rather than matrix stiffness. 49 Integrin β1 can activate the phosphorylation of FAK, which then leads to the activation of downstream intracellular signaling pathways, such as Ras/ mitogen activated protein kinase (MAPK), PI3K/Akt signaling pathways, etc. 50,51 In addition, studies have found that laminin proteins regulate the early osteogenic differentiation of stem cells by regulating the integrin α2β1 and FAK/extracellular regulated protein kinases (ERK) signaling pathways.…”
Section: Papermentioning
confidence: 99%
“…Recent studies suggest that synergetic effects on enhancing osteogenesis can be achieved by the combination of different size-scaled topological cues. Tian et al [144] investigated the effects of implant surface with a hierarchical microgroove/nanopore topography on osteogenesis, and demonstrated that such micro/nano-topographical surface showed enhanced cell adhesion and osteogenic efficiency due to the activated α2-PI3K-Akt pathway. Liu et al [145] identified the different cell polarization behaviours and the downstream effects driven by space constraint and adhesion induction via a substrate groove arrays from nano to microsize, revealing the different mechanisms causing cell polarization in these two cases.…”
Section: Mechanotransduction and The Related Signalling Pathwaysmentioning
confidence: 99%
“…Tian et al. [144] investigated the effects of implant surface with a hierarchical microgroove/nanopore topography on osteogenesis, and demonstrated that such micro/nano‐topographical surface showed enhanced cell adhesion and osteogenic efficiency due to the activated α 2‐PI3K‐Akt pathway. Liu et al.…”
Section: Cellular Functions Regulated By Micro/nano‐topographical Bio...mentioning
confidence: 99%
“…Enzymes are used in conventional cell culture protocols to release the cells during harvesting, though these enzymes reduce the cells’ functionality such as proliferation rate or viability due to the digestion of proteins [5] , [6] , [7] , [8] , [9] , [10] . Additionally, there are many studies reporting the improvement of cell adhesion on novel materials to produce new biomaterials or to generate cell aggregates for tissue engineering [11] , [12] . Despite such attention, there are few technologies to measure cell adhesion, and none known to the authors that are broadly useful or provide adhesion measurements without contact.…”
Section: Introductionmentioning
confidence: 99%